Evaluating sectoral innovation system functional performance in the additive manufacturing sector: cemented tungsten carbides case studies - Mc Clelland, Michelle (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.